2022
DOI: 10.1111/apm.13219
|View full text |Cite
|
Sign up to set email alerts
|

BUB1 predicts poor prognosis and immune status in liver hepatocellular carcinoma

Abstract: Background: Accurate assessment of the tumour immune microenvironment helps develop individualised immunotherapy regimens and screen dominant populations suitable for immunotherapy. Therefore, potential molecular markers were investigated to make an overall assessment of the immune microenvironment status of liver hepatocellular carcinoma (LIHC).Methods: Differentially expressed genes (DEGs) in LIHC were extracted from the International Cancer Genome Consortium and The Cancer Genome Atlas databases. Gene set e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…BUB1 was found to modulate the G2/M transition to promote the proliferation of non-muscle-invasive bladder cancer cells [ 14 ] and drove the progression and proliferation of bladder cancer by regulating the transcriptional activation of STAT3 signaling [ 15 ]. Moreover, BUB1 promotes the proliferation and vertical migration ability of liver cancer cells by activating phosphorylation of SMAD2 [ 16 , 17 ]. DUXAP8 serves as a sponge of MiR-490-5p to promote the expression of BUB1 in hepatocellular carcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…BUB1 was found to modulate the G2/M transition to promote the proliferation of non-muscle-invasive bladder cancer cells [ 14 ] and drove the progression and proliferation of bladder cancer by regulating the transcriptional activation of STAT3 signaling [ 15 ]. Moreover, BUB1 promotes the proliferation and vertical migration ability of liver cancer cells by activating phosphorylation of SMAD2 [ 16 , 17 ]. DUXAP8 serves as a sponge of MiR-490-5p to promote the expression of BUB1 in hepatocellular carcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Song et al 22 uncovered that BUB1 could serve as a possible oncogene for neuroblastoma. Qi et al 23 found that BUB1 could act as a probable prognostic biomarker for liver hepatocellular carcinoma. Balasundaram et al 5 confirmed that BUB1 is overexpressed in RA, which may be linked with the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 27 prognostic DECRs, 23 risk and 4 protective CRs were identified. At present, many of these 27 prognostic CRs we identified have been shown to have correlations with prognosis in some cancers [ 48 52 ]. For example, CBX6 and CBX7 were identified as prognostic biomarkers in bladder cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTK was identified as a prognostic biomarker in NSCLC [ 51 ]. BUB1 was found as a prognostic factor for hepatocellular carcinoma [ 52 ]. In addition, some new prognostic CRs have also been identified in LUAD, such as NPAS2 and HMGA2 [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%